"Vertical Relationships in the Ready‐to‐Eat Breakfast Cereal Industry in Boston". Issue 4 (3rd September 2013) - Chidmi, Benaissa
ABSTRACT This study examines the vertical relationship between manufacturers and retailers in the ready‐to‐eat cereal (RTEC) industry in Boston. More precisely, the questions to be answered are, "What kind of vertical relationship exists between the manufacturers and the retailers?" "Does this relationship support the high price‐cost margins in the RTEC industry?" The results indicate that the RTEC manufacturers have the pricing decisions and that the retailers do not intervene in setting the retail prices for breakfast cereal brands. This is consistent with the vertical restraints theory that helps the manufacturers eliminate the externality created by the double marginalization scenario and an excessive demand contraction. "Vertical Relationships in the Ready‐to‐Eat Breakfast Cereal Industry in Boston" appeared in Volume 28, Number 3 (Summer 2012).